1999
DOI: 10.1046/j.1365-2044.1999.00709.x
|View full text |Cite
|
Sign up to set email alerts
|

Meeting the standards for interhospital transfer of adults with severe head injury in the United Kingdom

Abstract: In December 1996, the Association of Anaesthetists of Great Britain and Ireland produced a series of recommendations outlining the safe conduct of interhospital transfers for patients with acute head injuries. We assessed the current ability of UK hospitals to implement these recommendations and opinions on the formation of transfer teams, using a postal questionnaire. This was sent to all Royal College of Anaesthetists tutors, 268 of whom replied (94% response rate). Of the hospitals surveyed, 208 received ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…Our results show that only 28% of NHS hospitals provide adequate personal injury insurance to their staff during transfer, which is in agreement with the findings of Knowles et al 8 who reported a figure of 27%. Anaesthetic trainees are encouraged by their consultants to join either the Association of Anaesthesists of Great Britain & Ireland or the Intensive Care Society for additional life and personal injury insurance.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our results show that only 28% of NHS hospitals provide adequate personal injury insurance to their staff during transfer, which is in agreement with the findings of Knowles et al 8 who reported a figure of 27%. Anaesthetic trainees are encouraged by their consultants to join either the Association of Anaesthesists of Great Britain & Ireland or the Intensive Care Society for additional life and personal injury insurance.…”
Section: Discussionsupporting
confidence: 93%
“…Most transfer patients are accompanied by junior trainees in anaesthetics, most commonly senior house officers (58%)14 or, in some cases (13%), the accompanying junior staff have <2 years postgraduate experience 8. This is much below the published recommendations,10 – 12 despite the available evidence that transfer by doctors lacking suitable experience may result in a higher incidence of life-threatening complications 20.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…4 Previous publications have suggested that standards of care are suboptimum. [5][6][7] While previous studies have analysed, for example, head injury transfers from an anaesthetic perspective, 8 there is a lack of available data on current levels and standards of transfer specific equipment in UK EDs. Similarly, there is little information on the current organisation and processes of care, staff training systems, and documentation for transportation of the critically ill to and from UK EDs.…”
mentioning
confidence: 99%